Modeling malaria incidence in North-Western Thailand - Sriwattanapongse W. (2014)
The transmission of malaria in Thailand is common, particularly in the North-western region of the country. The objective of this study is to identify the patterns of hospitaldiagnosed malaria incidences in districts and quarterly periods in the North-western region of Thailand in 1999-2004. Regression models based on principal components describe these patterns. The models show trends and spatial variations in disease incidence. Graphical displays showing both regional and period effects are presented. The results of this study show that malaria incidence rates decreased substantially in most districts during the study period, but remained very high in border districts with Myanmar.